The economic factor and its effect of the authority system: The Kurdish emirates during the Abbasid era as an example. Which is analyzed per Ebn Khaldon theory - Sayida, Ibrahim; Abdullah, Kamran (Humanities Journal of University of Zakho, 2023)
The appearance of the economic factor on the authority and citizens after the increase of civilization and welfare of economic situation of the domesticated tribal which started to establish system of authority and build castles, walls and cities for protecting itself from the outside attacks and assaults. This research entitled “the economic factor and its effect of the authority system”, the Kurdish emirates during the Abbasid era as an example. Which is analyzed per Ebn Khaldon theory. The research consists of two sections, in the first section we spoke about three points, which are, first the appearance the rank of Amir between the tribal leaders as the earliest stages of authority. Second the establishment of the rank of Minister to improve the administration and citizen life situation and other administration related work like collecting taxes. Third the establishment of the Judge rank which was one of the socialized positions to retrieve people rights and prohibit people to assault each other’s rights, and to do religious and social affairs. In the second section, we spoke about the place of Amir ruling, including the castles which was a symbol to improved political and economic situation. Also, the cities which was an important stage for the movement of Kurds from Urban to cities, and the appearance of the desire construction and prosperity specially by the Amirs and also building royal mansions.